Pengaruh Berbagai Dosis Kotoran Ayam terhadap Pertumbuhan dan Hasil Tanaman Bawang Merah (Allium ascalonicum L.) Varietas Bauji Menggunakan Polybag - Amelia, Imas; Susilawati, Susilawati; Irmawati, Irmawati (Seminar Nasional Lahan Suboptimal, 2023)
Amelia, I., Susilawati, S., & Irmawati, I. (2023). The effect of various doses of chicken manure on the growth and yield of shallot plants (Allium ascalonicum L.) bauji varieties use polybags. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang  21 Oktober 2023. (pp. 405-416). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Providing organic fertilizer is important for shallot plants (Allium ascalonicum L.) because organic fertilizer has advantages compared to inorganic fertilizer, namely that it is more environmentally friendly and safe when applied to soil media. One type of organic fertilizer that is often used by farmers is chicken manure. Chicken manure contains quite high levels of nitrogen, phosphorus and potassium nutrients which are useful for shallot plants. This research aimed to determine the best dose of chicken manure for the growth and yield of shallot plants (Allium ascolanicum L.) of the bauji variety. The research was carried out at the Sriwijaya University Campus Experimental Garden, South Sumatra at the coordinates 3 13'29.74”S 104 38'54.13”E which was carried out in June-August 2023. The design used was a Randomized Block Design (RBD) with 3 replications. The dose of chicken manure used is 10 tons/ha (40 g/polybag); 20 tons/ha (80 g/polybag); 30 tons/ha (120 g/polybag) and without chicken manure as a control. Parameters observed included leaf length, number of leaves, number of tillers, leaf greenness level, total chlorophyll content, leaf area, root length, number of tubers, tuber diameter, tuber length, tuber volume, fresh weight of tubers, dry weight of tubers, fresh weight, bushmeat and dry weight of bushmeat per plant. The results of the study showed that the application of chicken manure had a significant effect on the growth and yield of shallot plants. Giving chicken manure at a dose of 120 g/polybag resulted in better number of leaves, leaf greenness, leaf area, number of tubers and tuber production compared to giving other doses of chicken manure.